British Olympic hopefuls: The antecedents and consequences of implicit ability beliefs in elite track and field athletes - Jowett, N.; Spray, C. M. (Psychology of Sport and Exercise, 2013)
Objectives: This study provided an in-depth examination of the implicit ability beliefs held by elite British track and field athletes, including the antecedents and consequences of these beliefs. Design and Methods: A qualitative design was employed involving semi-structured interviews with 4 Olympic hopefuls in the sport of track and field athletics. Thematic analysis was utilised to interpret the results of the study, involving a combination of inductive and deductive approaches. Results: The core components of ability beliefs included beliefs that ability is stable, ability is malleable, and that it is possible to build on natural ability. A variety of personal, social and environmental antecedents appeared to influence the athletes' ability beliefs. The consequences of implicit beliefs encompassed three major themes, which were achievement motivation, setbacks and attributions for success and failure. Conclusions: The results from the analysis indicated that the athletes' implicit beliefs were very specific, as their beliefs about ability appeared to underpin sport-specific performance. The belief that ability was malleable was universal amongst the athletes and this may be related to their age, experience, high perceived ability and the high level at which they compete. However, the athletes believed that although natural ability is useful, talent is only a small part of the equation as learning, improving and working hard are all necessary for success at the highest level.